(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2012)
The researchers have a special interest in studying Markov chains as one of the probability samples which has many applications in different fields. This study comes to deal with the changes issue that happen on budget expenditures by using statistical methods, and Markov chains is the best expression about that as they are regarded reliable samples in the prediction process. A transitional matrix is built for three expenditure cases (increase ,decrease ,stability) for one of budget expenditure items (base salary) for three directorates (Baghdad ,Nineveh , Diyala) of one of the ministries. Results are analyzed by applying Maximum likelihood estimation and Ordinary least squares methods resulting a stable transitional probability matrix and predicting each studied case and any behavior may take in the future.